2020
DOI: 10.14444/7032
|View full text |Cite
|
Sign up to set email alerts
|

Outcome of Posterior-Only Approach for Severe Rigid Scoliosis: A Retrospective Report

Abstract: Background: The management of severe scoliosis may lead to significant complications, and adequate mobilization is a key step to achieve maximal correction, usually requiring extensive approaches. There is still no consensus on the management of these severe and rigid curves. In this study we evaluated the clinical and radiologic outcome of a posterior-only approach with multilevel asymmetric Ponte osteotomy with a minimum of 2 years' followup.Methods: In this retrospective study, 23 patients with severe and r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 37 publications
1
16
0
Order By: Relevance
“…To date, there have been many surgical approaches to treat severe spinal deformities, including preoperative traction followed by posterior instrumentation, combined anterior and posterior procedure, PSO or VCR by posterior procedure [ 7 , 10 , 20 ]. PVCR has been widely reported to treat severe rigid spinal deformity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To date, there have been many surgical approaches to treat severe spinal deformities, including preoperative traction followed by posterior instrumentation, combined anterior and posterior procedure, PSO or VCR by posterior procedure [ 7 , 10 , 20 ]. PVCR has been widely reported to treat severe rigid spinal deformity.…”
Section: Discussionmentioning
confidence: 99%
“…It is essential to develop detailed surgical plans based on the curve's location, magnitude, and stiffness prior to surgery. More and more evidences have shown that posterior-only osteotomy and instrumented fusion have excellent surgical outcomes in recent years [ 6 10 ]. The posterior vertebral column resection (PVR) involves removing one or more vertebrae to improve trunk balance and curvature correction.…”
Section: Introductionmentioning
confidence: 99%
“…All patients in surgery group underwent a single‐staged posterior‐only approach surgery with pedicle screws and titanium alloy 2‐rod system according to the guidelines described by Lenke [17]. During surgery, multilevel Ponte osteotomy was performed if there existed severe and rigid curves [18].…”
Section: Methodsmentioning
confidence: 99%
“…In fact, the management of scoliotic patients with severe curves may lead to significant complications related to extended exposure and blood loss, cord injury, and pulmonary compromise. [ 1 ] The goal of operative treatment is to obtain an acceptable correction of the deformity, to improve the patient's quality of life and cardiopulmonary status, and to prevent painful degeneration and curve progression. [ 2 ]…”
Section: Introductionmentioning
confidence: 99%